Critical Analysis of Patent Laws in Pakistan Since Independence - Allauddin, Hina; Anwar, Zahid (Qlantic Journal of Social Sciences, 2022)
Intellectual property is the creative expression based on which there is the public willingness to bestow the status of the property and a patent is a recognition of an invention, which satisfies the criteria of novelty, non-obviousness, and industrial application. This paper aims to discuss the evolution of Patent laws in Pakistan. It primarily looks into the transitional phases of the patent to remain in line with the international agreement i.e. Trade-Related Aspects of Intellectual Property laws. It then examines the extent to which safeguards have historically been used in patent laws for public interest and also to meet policy objectives. This research further aimed to trace out the discrepancies in the patent law, if any, to bring those issues into the limelight and thereafter to suggest recommendations to upgrade the law accordingly. For this purpose, the available literature was reviewed through a hand search method i.e.research articles, books and websites were explored and after in-depth analytical reading, the main themes were extracted for this study. The findings indicated that the Patent Law of Pakistan is at par with the set international norms, however, there is always space for improvement to keep at par with the set international standards.